2017
DOI: 10.5812/semj.57582
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting in Adoption and Use of Electronic Medical Record Based on Unified Theory of Acceptance and Use of Technology in Iran

Abstract: Background: One of the effective factors in successful implementation of health information technology, especially electronic medical record, is investigation of adoption and its use by users. Therefore, the aim of this study was to investigate factors affecting adoption and use of electronic medical record in Shiraz teaching hospitals from the perceptive of top and middle managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(19 reference statements)
2
12
0
1
Order By: Relevance
“…Nematollahi et al . in their study concluded that demographic variables do not impact the adoption of electronic medical records;[ 24 ] a finding, which is similar to the results of the present study. With regard to the study population features, for medical students who had similar educational levels and were most familiar with mobile health technology, the demographic information had no effect on their mobile health acceptance.…”
Section: Discussionsupporting
confidence: 91%
“…Nematollahi et al . in their study concluded that demographic variables do not impact the adoption of electronic medical records;[ 24 ] a finding, which is similar to the results of the present study. With regard to the study population features, for medical students who had similar educational levels and were most familiar with mobile health technology, the demographic information had no effect on their mobile health acceptance.…”
Section: Discussionsupporting
confidence: 91%
“…Nine studies [3], [4], [9], [20], [21], [29], [30], [31], [32] appropriately covered evaluation measures in the technology aspect. In human and organization aspects, the coverage rate of evaluation measures in six [23], [24], [33], [34], [35], [36] and four studies [9], [20], [37], [38] was better than other studies, respectively. Almost 40% of evaluations measures related to the human and organization aspects were covered by these studies.…”
Section: Coverage Rate Of Evaluation Measures In Identified Studies (Framework)mentioning
confidence: 78%
“…Z8, on the other hand, illustrates studies with moderate and low coverage in the technology and organization aspects, respectively. Nematollahi et al [34] In this table dimensions related to technology, human, and organization aspects were reported as following abbreviation, T1-T3 and TT for technology aspect, H1-H5 and TH for human aspect, and O1-O4 and TO for organization aspect. In this table, the coverage rate of evaluation measures was represented by color cells.…”
Section: Coverage Rate Of Evaluation Measures In Identified Studies (Framework)mentioning
confidence: 99%
“…Venkatesh et al, (2003) identified four key moderators believed to influence the relation between major determinants and intentions: gender, age, voluntariness, and experience. Nematollahi et al, (2017) results showed that there is a direct positive relation between Effort Expectancy and Behavioral Intention (p = 0.01) as well as between facility conditions and behavioral intention (p = 0.04) and between facility conditions and Use behavior (p = 0.01). In addition, there is a direct and positive relation between behavioral intention and use behavior.…”
Section: Resultsmentioning
confidence: 95%